2000
DOI: 10.1111/j.1939-1676.2000.tb02281.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Serum Alkaline Phosphatase Activity in Canine Appendicular Osteosarcoma

Abstract: Sixty-one dogs with appendicular osteosarcoma were treated with amputation and chemotherapy of cisplatin and doxorubicin. Serum samples were obtained before and after treatment for determination of total alkaline phosphatase (TALP) activity as well as the activities of the constituent bone (BALP), liver (LALP), and corticosteroid-induced (CALP) isoenzymes. The relationship between alkaline phosphatase activities and survival was examined by Cox proportional hazards regression analysis and KaplanMeier log rank … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
41
3
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 25 publications
(18 reference statements)
5
41
3
3
Order By: Relevance
“…A few previous studies 7,8 have identified increased total (or serum) alkaline phosphatase activity as a negative prognostic factor. However, in the cohort of dogs in the present study, an increased total alkaline phosphatase activity was not identified as affecting survival time beyond 1 year, a finding supported in another study.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…A few previous studies 7,8 have identified increased total (or serum) alkaline phosphatase activity as a negative prognostic factor. However, in the cohort of dogs in the present study, an increased total alkaline phosphatase activity was not identified as affecting survival time beyond 1 year, a finding supported in another study.…”
Section: Discussionmentioning
confidence: 94%
“…2,8,12–15 Amputation of the affected limb is generally recommended in those patients in which orthopedic and neurologic disease in other limbs does not prevent the use of this procedure. 12,15 Alternatively, a wide variety of limb-sparing surgical techniques have been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with that, no mutation has been recently identified in canine β-catenin exon 3, similarly to human OSA [19], even if a limited number of cases were examinated, and a mainly cytoplasmic, but rare nuclear localization of the protein was detected [51]. Furthermore, no differences in nuclear β-catenin immunohistochemical expression were observed in samples obtained from two populations of canine OSA patients with normal or high level of serum alkaline phosphatase concentration [52], known to have negative prognostic value in canine osteosarcoma patients [53]. These results seem to be in agreement with recent investigations in human OSA [26], where no β-catenin nuclear expression was observed in 90% of human high grade OSA biopsies examinated and inhibition of the Wnt/β-catenin pathway has been demonstrated to be important in osteoblast neoplastic transformation [26].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the Abrams cell line produced large colonies in soft agar, indicating capability of anchorage-independent growth with little contact inhibition, indicative of carcinogenesis and metastatic potential. Only the Abrams cells consistently stained positively for alkaline phosphatase, an enzyme used to differentiate OSA from other soft tissue tumors on histopathology, and one that is often used to correlate with prognosis in OSA patients 7,11,20,21. In some studies, elevated serum levels of alkaline phosphatase are correlated with approximately 50% shorter survival times despite assertive treatment 7,11,19…”
Section: Discussionmentioning
confidence: 99%